First Impressions on Information Economic Variables : A Comparative Study between Turkey and OECD Countries (1995-1999) - Yeloğlu, Hakkı Okan (Information World, 2009)
The gradual growth in the importance of Information Economics, especially in late 1990s; has led to different research inquiries along with broadened study fields. In addition, there have been continuous disputes on subjects like; how “an information economy” should be defined theoretically, and with which variables can its intensity and characteristics be measured. Thereby, this study covers both the possible variables that build up the information technology, and also it aims to set forth a positioning, by means of comparing Turkey with other countries. Furthermore, in the context of information technology, it has been intended to designate Turkey’s resemblance to other countries in due course, in terms of its information and communication-based technological activities. This study conceives OECD’s (Organisation for Economic Co-operation and Development) criteria for an information economy assessment, and conducts an empirical research. Throughout the study, it has been identified that, in terms of the progress exhibited by Turkey mostly bears resemblance to North European countries, according to the findings which were obtained by using hierarchical cluster analysis.
Keywords: Information economy; OECD; Turkey